ANALISIS PENGGUNAAN RUBU MUJAYYAB MENURUT TERJEMAHAN KITAB TAQRIBUL MAQSHAD DALAM MENGKALIBRASI ARAH KIBLAT TPU TOMBO-TOMBOLO DI DESA GUNUNG SILANU, KEC. BANGKALA, KAB. JENEPONTO - Utari, Azizah Nurul; Akmal, Andi Muhammad (HISABUNA: Jurnal Ilmu Falak, 2025)
The Qibla is the direction to the house that Muslims need to pay attention to, because it is an obligation and a legitimate requirement in the practice of worship and the necessity to confront the body in its direction. Thus, over time, various methods of determination were born to make it easier for Muslims about where the Qibla is headed. This study further reviews the accuracy of rubu mujayyab refers to the classic method of the taqribul maqshad guidebook in the current era by using TPU Tombo-Tombolo coordinate data. This research is field-based, with Syar'i, sociological and astronomical approaches. Primary Data obtained from observations through the process of calibrating the direction of the Qibla. The results of this study indicate that the method of Qibla direction using rubu mujayyab refers to taqribul maqshad is fairly complicated for beginners when viewed from the past era, but in the present era is quite practical in the understanding by the public because latitude and longitude do not need to be calculated manually. after the measurement using TPU Tombo-Tombolo coordinate point produces Qibla azimuth with rubu mujayyab on taqribul maqshad which is 289° while kotemporer-based sun compass shows 292° so that the difference is 3°. The difference produced by the method of taqribul maqshad is also erratic and can change if using the coordinate data of other areas, this can happen because the calculation is based on the classical hisab Hakiki bi-al taqribi (approximately). The implications of this study hope to contribute to the educational understanding of determining the direction of Qibla to the surrounding community, both classical and modern that they can easily understand, it is also expected that students in the field of astronomy are not too inclined to modern tools, so that classical tools are not drowned by the times because they have an important history in the development of astronomy and are the legacy of muslim scientists who can still be used as scientific isnaad.